2016
DOI: 10.1037/sgd0000184
|View full text |Cite
|
Sign up to set email alerts
|

Centralizing the psychology of sexual minority Asian and Pacific Islander Americans.

Abstract: The purpose of this literature review article was to centralize a holistic view of sexual minority Asian and Pacific Islander American (SM APIA) experiences and offer recommendations to guide psychological practice. Theoretical and empirical works from various disciplines were synthesized and found to demonstrate the central role of API cultural values in the development and management of SM APIA sexual expressions. Connectedness to communities and cultures of origin, maintenance of prized social relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 100 publications
(329 reference statements)
0
15
0
Order By: Relevance
“…Sexual/gender minority identities are perceived in Asian American cultures as interfering with family obligations, such as fulfilling marriage and reproduction responsibilities, and enhancing a family's reputation in the community (Choudhury et al, 2009). Open identification with one's sexual/gender minority identity is often seen as unnecessary for social functioning, and sexual restraint is generally positively reinforced (Choi & Israel, 2016;Okazaki, 2002).…”
Section: Structural/cultural Factorsmentioning
confidence: 99%
“…Sexual/gender minority identities are perceived in Asian American cultures as interfering with family obligations, such as fulfilling marriage and reproduction responsibilities, and enhancing a family's reputation in the community (Choudhury et al, 2009). Open identification with one's sexual/gender minority identity is often seen as unnecessary for social functioning, and sexual restraint is generally positively reinforced (Choi & Israel, 2016;Okazaki, 2002).…”
Section: Structural/cultural Factorsmentioning
confidence: 99%
“…Yip (2005) highlighted that contextual variables, such as the presence of out-group members, may heighten the salience of one’s minority identity. Furthermore, ethnocultural communities and families of origin often provide significant buffers against discrimination related to racism insofar as heteronormativity is assumed (Choi & Israel, 2016) whereas with Asian LGBTQ identities, individuals often face marginalization and stigmatization within their cultural groups in addition to the larger social context (Ching et al, 2018). An appreciation of such layered intersections of culture, gender, and related situational variables is important to increasing our understanding of the salience and centrality of one’s marginalized identities to their overall sense of self.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the “Asian” identifier refers to individuals whose origins are rooted in East, South, and South-East Asian countries. This is a highly diverse group whose ethno-racial, sexual, and gender identities involve a complex and idiosyncratic mix of personal and intergenerational influences (e.g., colonialism, education, immigration experiences, traditional or religious doctrines; Ching et al, 2018; Choi & Israel, 2016; Chung & Singh, 2009; Nadal & Corpus, 2013), as well as shared cultural commonalities (Hayashino & Chopra, 2009; Szymanski & Sung, 2013). One commonality is a collectivistic orientation, which places more importance on relationships, familial commitments, and the maintenance of outward traditional roles (such as traditional gender role expectations).…”
Section: Cultural and Familial Considerationsmentioning
confidence: 99%
“…Originally developed for use with sexual minority populations, the minority stress framework asserts that individuals with minority statuses experience distal stressors (e.g., discrimination and prejudice) that then lead to proximal stressors (e.g., shame, fear of prejudice, and identity concealment), which manifest into experiences of stress and long-term health implications. Previous studies have found support for the minority stress framework with LGBT Asian Americans (for a review, see Choi & Israel, 2016). This research is crucial given that LGBT Asian Americans are exposed to unique adverse experiences that are not shared by their heterosexual or White counterparts (Nadal et al, 2015) and are disproportionately impacted by minority stressors, even compared to other queer people of color (Balsam et al, 2011).…”
Section: Current Studymentioning
confidence: 99%
“…This research is crucial given that LGBT Asian Americans are exposed to unique adverse experiences that are not shared by their heterosexual or White counterparts (Nadal et al, 2015) and are disproportionately impacted by minority stressors, even compared to other queer people of color (Balsam et al, 2011). Furthermore, LGBT Asian Americans can be considered a doubly invisible group whose views and experiences are rarely documented and frequently erased (Choi & Israel, 2016), in which the intersectional mechanisms that underlie their oppression have not been fully explored, especially from a quantitative perspective.…”
Section: Current Studymentioning
confidence: 99%